Protective Role of Decorin in Primary Hepatocellular Carcinoma - Reszegi, Andrea; Horváth, Zsolt; Fehér, Hajnalka; Wichmann, Barnabás; Tátrai, Péter; Kovalszky, Ilona; Baghy, Kornélia (Frontiers in Oncology, 2020)
Hepatocellular carcinoma (HCC) represents one of the most frequent type of primary liver cancers. Decorin, a small leucine-rich proteoglycan of the extracellular matrix, represents a powerful tumor cell growth and migration inhibitor by blocking various receptor tyrosine kinases and inducing p21WAF1/CIP1. In this study, first we tested decorin expression in HCCs utilizing in silico data, as well as FFPE samples of HCC in a tissue microarray. In silico data revealed that DCN/SMA mRNA ratio is decreased in HCC compared to normal tissues, and follows the staging of the disease. Among TMA samples 52% of HCCs were decorin negative, 33% exhibited low, and 15% high decorin levels corroborating in silico results. In addition, applying conditioned media of hepatoma cells inhibited decorin expression in LX2 stellate cells in vitro. These results indicate that decorin may act as a tumor suppressor in liver cancer as its expression is reduced or completely blocked in HCC. To further test the protective role of decorin, the proteoglycan was overexpressed in a mouse model of hepatocarcinogenesis evoked by thioacetamide (TA). After transfection, the excessive proteoglycan amount was mainly detected in hepatocytes around the central veins. Upon TA-induced hepatocarcinogenesis the highest tumor count was observed in mice with no decorin production. Decorin gene delivery reduced tumor formation, in parallel with decreased pEGFR, increased pIGF1R levels, and with concomitant induction of pAKT(T308) and phopho-p53, suggesting a novel mechanism of action. Our results support the idea of decorin utilization as an anti-cancer agent in the battle of liver malignancies.